Independent and coherent transitions between antiferromagnetic states of few-molecule systems - Besson, Claire; Stegmann, Philipp; Schnee, Michael; Zanolli, Zeila; Achilli, Simona; Wittemeier, Nils; Vierck, Asmus; Frielinghaus, Robert; Kögerler, Paul; Maultzsch, Janina; Ordejón, Pablo; Schneider, Claus M.; et al. (Physical Review B, 2023)
Spin-electronic devices are poised to become part of mainstream microelectronic technology. Downsizing them led to the field of molecular spintronics. Here, we provide proof-of-concept data that allow expanding this area from its traditional focus on single-molecule magnets to molecules in which spin centers are antiferromagnetically (AFM) coupled to result in a singlet ground state. In this context, and in contrast to all previous work on molecular spintronics, we develop a detection scheme of the spin state of the molecule that does not rely on a magnetic moment. Instead, we use quantum dot devices consisting of an isolated, contacted single-wall carbon nanotube covalently bound to a limited number of molecular AFMs, for which we chose representative coordination complexes incorporating four Mn(II) or Co(II) ions. Time-dependent quantum transport measurements along the functionalized nanotube show steplike transitions between several distinct current levels that we attribute to transitions between different AFM states of individual molecular complexes grafted on the nanotube. A statistical analysis of the switching events using factorial cumulants indicates that the cobalt complexes switch independently from each other, whereas a coherent superposition of the AFM spin states of the molecules along the nanotube is observed for the manganese complexes. The long coherence time of the superposition state (several seconds at 100 mK) is made possible by the absence of spin and orbital momentum in the relevant states of the manganese complex, while the cobalt complex includes a significant orbital momentum contribution due to the pseudo-octahedral coordination environment of the d7 metal centers.
CRIS-Team Scopus Importer:2023-08-04